Computed tomography imaging‐identified location and electrocardiographic characteristics of left bundle branch area pacing in bradycardia patients. (30th April 2022) - Chen, Keping; Liu, Xingbin; Hou, Xiaofeng; Qiu, Yuanhao; Lin, Jinxuan; Dai, Yan; Xu, Yuanning; Jiang, Lingyun; Zhou, Xiaohong; Zhang, Xue; Lu, Hongyang; Mara, Nicki; et al.
Abstract: Introduction: Left bundle branch area pacing (LBBAP) is a novel physiological pacing modality. The relationship between the pacing lead tip location and paced electrocardiographic (ECG) characteristics remains unclear. The objectives are to determine the lead tip location within the interventricular septum (IVS) and assess the location‐based ECG QRS duration (QRSd) and left ventricular activation time (LVAT). Methods: This multicenter study enrolled 50 consecutive bradycardia patients who met pacemaker therapy guidelines and received LBBAP implantation via the trans‐ventricular septal approach. After at least 3 months postimplant, 12‐lead ECGs and pacing parameters were obtained. Cardiac computed tomography (CT) imaging was performed to assess the LBBAP lead tip distance from the LV blood pool. Results: Among the 50 patients, analyzable CT images were obtained in 42. In 23 of the 42 patients, the lead tips were within 2 mm to the LV blood pool (the LV subendocardial (LVSE) group), 13 between 2 and 4 mm (the Near‐LVSE group), and the remaining 6 beyond 4 mm (the Mid‐LV septal (Mid‐LVS) group). No significant differences in paced QRSd were found among the three groups (LVSE, 107 ± 15 ms; Near‐LVSE, 106 ± 13 ms; Mid‐LVS, 104 ± 15 ms; p  = .87). LVAT in the LVSE (64 ± 7 ms) was significantly shorter than in the Mid‐LVS (72 ± 8 ms; p  < .05), but not significantly different from that in the Near‐LVSE (69 ± 8 ms; p  > .05). Conclusion: In routine LBBAP practice, paced narrow QRSd and fast LVAT, indicative of physiological pacing, were consistently achieved for lead tip location in the LV subendocardial or near LV subendocardial region.